Growth and Yield of Sunflower (Helianthus annuus L.) Hybrids under Different Nutrient Management Practices - Pattanayak, Sarthak; Behera, Aswini; Jena, S. N.; Das, Priyanka; Behera, Suryakanta (International Journal of Bio-resource and Stress Management, 2023)
Field experiment conducted at Department of Agronomy, College of Agriculture, Orissa University of Agriculture and Technology, Bhubaneswar, (India) under split plot design taking four nutrient management practices including combination of recommended dose of fertilizer, application of ZnSO4 @ 25 kg ha-1, boron @ 1 kg ha-1 and biofertliser along with four genotypes including three hybrids and one local variety evaluated that application of recommended dose of fertilizer with dose of 80−60−80 kg N, P2O5, K2O+ZnSO4 @ 25 kg ha-1 recorded in higher plant height (160.3 cm), number of leaves (31.1), leaf area index (3.549) and dry matter accumulation (128.90 g plant-1) with higher crop growth rate (12.343 g m-2 d-1) as compared to other and also reported higher seed (2.17 t ha-1), Stover (4.88 t ha-1) and oil (0.91 t ha-1) yield, which was followed by application of recommended dose of fertilizer+boron 1 k ha-1. Hybrid Super-48 recorded higher growth and yield attributing characters as compared to others with plant height, number of leaves, leaf area index, dry matter accumulation, crop growth rate with corresponding values of 157.8 cm, 23.0, 3.572, 133.22 g plant-1 and 13.177 g d-1 m-2, respectively. Application of ZnSO4 25 kg ha-1 in hybrid Super-48 recorded the highest seed yield and oil due application of sulphur which was followed by application of boron 1 kg ha-1.